Peran Kepala Madrasah dalam Memotivasi Etos Kerja Guru di MTs Az zahro Prabumulih Sumatera Selatan - Fatimah Az-Zahro; Wasito Wasito (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
This study employed a qualitative research design with data collected through in-depth interviews, direct observations, and document analysis. The key informants comprised the principal, the vice principal for curriculum affairs, and teachers of MTs Az Zahro. Data were analyzed through processes of reduction, display, and conclusion drawing, while the credibility of findings was ensured through triangulation of sources and techniques. The results reveal that the principal fulfills an active role as a motivator, role model, and supervisor. He encourages teachers by adopting persuasive strategies, engaging directly in school activities, and providing recognition for strong performance. His democratic and communicative leadership style has fostered a positive and collegial working environment. The majority of teachers demonstrated a strong work ethic, reflected in their discipline, sense of responsibility, and enthusiasm for teaching. Nevertheless, a small number of teachers exhibited decreased motivation, attributed to professional fatigue or external challenges.